Review for Disease of the Year: Epidemiology of Juvenile Idiopathic Arthritis and its Associated Uveitis: The Probable Risk Factors. (June 2013) - Heiligenhaus, Arnd; Heinz, Carsten; Edelsten, Clive; Kotaniemi, Kaisu; Minden, Kirsten
Abstract Juvenile idiopathic arthritis (JIA) is the most common systemic disease associated with uveitis in childhood. The frequency of JIA-associated uveitis (JIAU) varies geographically, and between ethnicities. Uveitis risk is high in JIA associated with oligoarthritis, young age at arthritis onset and ANA positivity. Gender alters risk for the incidence of JIA and the severity of JIAU. Familial cases support the possible role of genetic influences in the pathogenesis. Arthritis typically precedes the uveitis, but uveitis may occur up to seven years following the arthritis onset. Although complications still occur, the frequency of bilateral blindness has dropped, probably by both improved screening of high-risk patients with JIA, and the increased use of early immunosuppression. However, there is still continuing persistence of JIAU into adulthood. For improvement of epidemiological knowledge of this complicated disease, large, well-defined, long-term population-based registries are needed with the application of universally agreed case definitions and outcome measures.